The Development of Computer Assisted Vocabulary Learning (CAVL) to Improve English Lexical Retention of Nursing Students - Kristanto, Barlian; Putri, Diannike; Dung, Le Huang; Flores, Michael John V.; Glomjai, Thanee; Suryani, Roro Lintang (JOLLT Journal of Languages and Language Teaching, 2024)
Vocabulary mastery is crucial for nursing students to effectively communicate in English. This study aimed to develop and validate a tailored computer-assisted vocabulary learning (CAVL) intervention to improve nursing students' retention of English lexicon, which is essential for healthcare communications. The CAVL program was designed using the Moodle platform and focused on four thematic units that targeted essential nursing vocabulary. The learning process followed research-based principles of vocabulary instruction, including multimodal introduction, reinforced retrieval, and contextual repetition. This study utilized a research and development methodology to conduct iterative needs analyses, design refinement, and rigorous evaluation protocols. Expert reviews, prototype testing, post-intervention vocabulary tests, and delayed assessments were used to gather data and make data-driven improvements. Quantitative analysis evaluated the effectiveness of this approach for 100 Indonesian nursing students. Vocabulary assessments were administered before, immediately after, and two weeks after the intervention, revealing significant improvements in terminology knowledge following the implementation of CAVL. Importantly, scores remained stable during the delayed assessment, demonstrating durable retention. These results are consistent with previous literature on the benefits of contextual and multimodal vocabulary learning. The CAVL prototype facilitated learning and effectively improved vocabulary retention outside of the classroom. This research provides an adaptable framework for technologically-assisted language mastery, which is essential for the next generation of nursing education. Further studies can explore the application of this framework in allied healthcare fields and the transition to practice in nursing education.Â 